2014
DOI: 10.1134/s0965545x14060133
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and the bulk rheological properties of the highly-branched block polyethers

Abstract: Several kinds of highly branched block polyethers were synthesized via anion ring opening poly merization of propylene oxide (PO) and ethylene oxide (EO), using phenol amine resin (PA) as the initiator. The rheological properties determined by rotational rheometer all followed the regular rules of polymer systems: under a certain conditions, the bulk polyethers were pseudoplastic and non Newtonian fluid, and with the increasing of the shear rate and temperature, the apparent viscosity of the block copolymers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(6 reference statements)
2
6
0
Order By: Relevance
“…The higher viscosity of DGEBA is due to hydrogen bonding which is why increasing the temperature slightly to 50°C reduces its viscosity sharply (the DGEBA contains oligomers with secondary hydroxyl groups). As temperature raised, the activity of molecular chain segments achieved enhancement, and the free volume became larger, which weaken the molecular interactions and also the decreasing entanglement density further leaded to the decrease of the flow resistance 44,45 . The significantly reduced viscosity of HPVIGEP was consistent with our original design goal of multi‐arm star molecular structure.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The higher viscosity of DGEBA is due to hydrogen bonding which is why increasing the temperature slightly to 50°C reduces its viscosity sharply (the DGEBA contains oligomers with secondary hydroxyl groups). As temperature raised, the activity of molecular chain segments achieved enhancement, and the free volume became larger, which weaken the molecular interactions and also the decreasing entanglement density further leaded to the decrease of the flow resistance 44,45 . The significantly reduced viscosity of HPVIGEP was consistent with our original design goal of multi‐arm star molecular structure.…”
Section: Resultssupporting
confidence: 77%
“…As temperature raised, the activity of molecular chain segments achieved enhancement, and the free volume became larger, which weaken the molecular interactions and also the decreasing entanglement density further leaded to the decrease of the flow resistance. 44,45 The significantly reduced viscosity of HPVIGEP was consistent with our original design goal of multi-arm star molecular structure.…”
Section: Rheological Behaviorsupporting
confidence: 75%
“…The reason for this result may be the small molecular weight of POEA relative to that of the high polymer. Yang et al 32 showed that the increase in the number of blocks and the EO content significantly affects the polyether's rheological performances and viscosity. Polyether viscosity increases with an increase of EO content.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The polyether demulsifier performs well in enhancing the demulsification of the IAA-stabilized (interfacially active asphaltenes) emulsion, achieving complete water removal of the emulsions in 30 min at 60 °C and 400 ppm . Polyether demulsifiers can be divided into amines, alcohols, alkyl phenol resins, phenolamine resins, and hydrogen-containing silicone oils according to different initiators. , Poly­(propylene oxide)–poly­(ethylene oxide) and poly­(propylene oxide)–poly­(ethylene oxide)–poly­(propylene oxide) (PPO–PEO and PPO–PEO–PPO, respectively) block polyethers have good compatibility, mainly through the polymerization reaction of the starting agent and propylene oxide and ethylene oxide, which played an important role in crude oil demulsification, emulsification cleaning, sewage treatment, and other areas. , The properties of block polyether surfactants are closely related to the structure of the initiator . Linear, multibranched, dendriform polymers can be synthesized according to the amount and location of active hydrogen in the initiator. , …”
Section: Introductionmentioning
confidence: 99%
“…32,33 The properties of block polyether surfactants are closely related to the structure of the initiator. 34 Linear, multibranched, dendriform polymers can be synthesized according to the amount and location of active hydrogen in the initiator. 35,36 Fluorinated polyether demulsifier is one of the most important special surfactants and has the highest activity.…”
Section: ■ Introductionmentioning
confidence: 99%